Design and software characterization of finFET based full adders - Raju Hajare; C. Lakshminarayana (Institute of Advanced Engineering and Science, 2019)
Adder is the most important arithmetic block that are used in all processors. Most of the logical circuits till today were designed using Metal Oxide Semiconductor Field Effect Transistors (MOSFET’s). In order to reduce chip area, leakage power and to increase switching speed, MOSFET’s were continuously scaled down. Further scaling below 45nm, MOSFET’s suffers from Short Channel Effects (SCE’s) which leads to degraded performance of the device. Here the Performance of 28T and 16T MOSFET based 1-bit full adder cell is characterized and compared with FinFET based 28T and 16T 1-bit full adders at various technology nodes using HSPICE software. Results show that FinFET based full adder design gives better performance in terms of speed, power and reliability compared to MOSFET based full adder designs. Hence FinFET are promising candidates and better replacement for MOSFET.